Feasibility accuracy of three-dimensional echocardiography colour flow measurement on duct pulmonary dependent circulation - Abdul Muhaimin,; Mazlyfarina Mohamad,; Haifa Abdul Latif,; Mazeni Alwi, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The assessment for patient with duct-dependent pulmonary circulation (DDPC) during the inter-stage intervals before first stage palliation commonly includes imaging of the heart with multiple imaging modalities. Recently, three-dimensional echocardiography (3DE) was found with the ability to delineate cardiac structure that is able to do 360o rotation. Therefore, this study aimed at identifying the accuracy of 3DE colour flow in measuring PDA size compared to computer tomography angiography (CTA). This study involves randomly selected 26 patients with DDPC undergoing CTA for palliation treatment in one year. The mean patient age is 1.6 ± 0.261 months with mean weight of 3.65 ± 0.82 kg. The full-volume 3DE colour flow acquisition was performed and analysed offline using Q-lab software. The PDA diameters at the origin as well as the insertion site were measured. The data obtained by 3DE colour flow data were compared to the CTA, which was taken as the gold standard. Results showed that the offline analysis of PDA size was feasible in all patients (100%) with the mean diameter of PDA at the origin on 3DE colour flow and CTA of 0.51 mm ± 0.14 and 0.52 mm ± 0.11, respectively (p = 0.92) . The PDA diameter at insertion site on 3DE colour flow and CTA was 0.29 mm ± 0.08 and 0.27 mm ± 0.97 respectively (p = 0.5). Meanwhile, the measurement of 3DE colour flow is comparable to CTA in measurement PDA size. However, the use of 3DE colour flow in infants with rapid heart rate is yet challenging to 3DE colour flow acquisitions.